A case report of appendiceal adenocarcinoma extending from the retroperitoneum to the psoas muscle. (April 2023) - Aljohani, Alaa; Alzarea, Abdulla; Al Jafar, Abdullah; Qabani, Hanan; Sairafi, Rami; Alzahrani, Ali
Abstract: Introduction: Invasive appendiceal adenocarcinoma is rare. We describe the first reported case of appendiceal adenocarcinoma invading the psoas muscle in a 27-year-old man. Case presentation: The patient presented with lower right quadrant pain, persisting since the last two months. Computed tomography revealed a retroperitoneal mass with a central calcified focus in the right iliac fossa, with a mass effect on the adjacent iliopsoas muscle and apparent invasion of the cecal wall. Clinical discussion: Magnetic resonance imaging showed a retrocecal appendicular mass with central necrosis. Colonoscopy showed an extra luminal mass effect that caused bulging of the ileocecal valve. Biopsy revealed lymphoid hyperplasia of the mucosa of the terminal ileum, with no malignant changes. An elective right hemicolectomy was done along with ileotransverse anastomosis. Histopathology examination of the surgical specimen revealed a moderately differentiated adenocarcinoma (Stage IV). Hence, adjuvant chemotherapy followed by hyperthermic intraperitoneal chemotherapy was employed. Conclusion: Non-specific symptoms and difficulties in reaching a diagnosis pre-operatively, may contribute to underreporting of appendiceal adenocarcinomas. Besides, few therapeutic options are available due to the rarity of this tumor. Complete surgical excision and/or chemotherapy may be lifesaving. Highlights: Appendiceal adenocarcinoma involving the psoas muscle is extremely rare, especially in younger patients of which this may be the first report. Appendiceal adenocarcinoma can be a challenging diagnosis often only made after appendicectomy, unless there is local invasion Surgical resection can be potentially curative and is the management of choice